Genetic diversity and connectivity of white shrimp (Penaeus merguiensis) in the North Coast of Central Java, Indonesia - JASIEL JUNIOR KAROSEKALI; DIAH PERMATA WIJAYANTI; DWI HARYANTI; YEFTA OLIVIA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Karosekali JJ, Wijayanti DP, Haryanti D, Olivia Y. 2026. Genetic diversity and connectivity of white shrimp (Penaeus merguiensis) in the North Coast of Central Java, Indonesia. Biodiversitas 27 (3): d270336. https://doi.org/10.13057/biodiv/d270336. White shrimp (Penaeus merguiensis) is one of the major capture fisheries commodities in Central Java and has been classified as fully exploited under the Minister of Marine Affairs and Fisheries Decree No. 19/2022. Therefore, this study aims to investigate genetic diversity and population structure to provide a reference for capture fisheries management. A total of 48 specimens were collected from Tegal and Rembang, while 70 sequences from Demak waters were obtained from GenBank. DNA was extracted using Chelex, amplified by PCR, and sequenced with the Sanger method targeting the mtDNA Cytochrome C Oxidase subunit I (COI) gene. Results showed high haplotype diversity, low nucleotide diversity, and high-significant population structure. Harpending's Raggedness Index and neutrality tests indicated an expanding population with negative results. However, the Demak population showed a deviation with significant raggedness due to a steep mismatch and low nucleotide diversity. The haplotype network showed population-specific clustering patterns radiating from a central ancestral haplotype, suggesting restricted gene flow among locations. These patterns are consistent with the combined effects of monsoon-driven currents, differences in fishing grounds, and overfishing, although these factors were not directly tested in this study. These findings highlight the need for population-specific management strategies and strict monitoring of fishing efforts to ensure the sustainability of P. merguiensis in Central Java, Indonesia.